Slosh Analyzes of a Full Vehicle-Tank Model with SDRE Control with a Hydraulic Damper - Lenz, Wagner B.; Ribeiro, Mauricio A.; Tusset, Angelo M.; Balthazar, Jose M. [UNESP]; Jarzebowska, Elżbieta (Springer Nature, 2021)
Slosh has been one of the main concerns for transportation vehicles, specifically with partially filled tanks trucks. The liquid movement due to changes of vehicle velocity magnitude and direction as well as external excitation can be the source of instability problems in trucks and passenger vehicles. Due to intrinsic characteristics, the natural frequency of sloshing is similar to the human input frequency, wind excitation and road displacement. Thus, managing and controlling the vehicle-tank system dynamics is required to maintain the desired safety standards. In this paper a numerical study of a quarter car vehicle-tank model is conducted by investigating motion of a linear pendulum model without baffles. A numerical analyses of the roll dynamics, bifurcation diagram and 0–1 test, is performed and a controller based upon the State-Dependent Riccati Equation method controlling the movement on the damper. The results demonstrate hat the pendulum model adequately maps the fluid behavior in the tank. Nevertheless, due to low dissipation of slosh motion, around the natural frequency the displacement increases significantly and the vehicle motion can cause loss of control and roll over. In this case, the passive control is unable to significantly reduce the slosh. Nevertheless, it significantly reduce the pendulum motion and avoids the overturn and improving the driviblility and safety.
Keywords: Control; Nonlinear dynamics; Slosh motion